Foci of contamination of Listeria monocytogenes in different cheese processing plants - Almeida, G. (2014)
Listeria monocytogenes is a ubiquitous bacterium widely distributed in the environment that can cause a severe disease in humans when contaminated foods are ingested. Cheese has been implicated in sporadic cases and in outbreaks of listeriosis worldwide. Environmental contamination, in several occasions by persistent strains, has been considered an important source of finished product contamination. The objectives of this research were to (i) evaluate the presence of L monocytogenes within the factory environments and cheeses of three processing plants, artisanal producer of raw ewe's milk cheeses (APC), small-scale industrial cheese producer (SSI) and industrial cheese producer (ICP) each producing a distinct style of cheese, all with history of contamination by L monocytogenes (ii) and identify possible sources of contamination using different typing methods (arsenic and cadmium susceptibility, geno-serotyping, PFGE). The presence of markers specific for 3 epidemic clones (ECI-ECIII) of L monocytogenes was also investigated: Samples were collected from raw milk (n = 179), whey (n = 3), cheese brining solution (n = 7), cheese brine sludge (n = 505), finished product (n = 3016), and environment (n = 2560) during, at least, a four-year period. Listeria monocytogenes was detected in environmental, raw milk and cheese samples, respectively, at 15.4%, 1.1% and 13.6% in APC; at 8.9%, 2.9% and 3.4% in SSI; and at 0%, 21.1% and 0.2% in ICP. Typing of isolates revealed that raw ewe's milk and the dairy plant environment are important sources of contamination, and that some strains persisted for at least four years in the environment. Although cheeses produced in the three plants investigated were never associated with any case or outbreak of listeriosis, some L monocytogenes belonging to specific PFGE types that caused disease (including putative epidemic clone strains isolated from final products) were found in this study.